2016
DOI: 10.4049/jimmunol.1401059
|View full text |Cite
|
Sign up to set email alerts
|

Splenic Long-Lived Plasma Cells Promote the Development of Follicular Helper T Cells during Autoimmune Responses

Abstract: Long-lived plasma cells (LLPCs) develop under the help of follicular helper T (Tfh) cells and reside mainly in the bone marrow. However, these cells are unusually abundant in the spleen of several autoimmune models including K/BxNsf mice, yet their pathogenic impact remains unknown. To investigate a previously unappreciated role of splenic LLPCs, we sorted splenic plasma cells (PCs) from K/BxNsf and K/BxN mice, corresponding to LLPCs and conventional short-lived PCs, respectively, and compared their phenotypes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 41 publications
2
8
0
Order By: Relevance
“…T cells, primed with DCs or LLPCs, but not with SLPCs, can provide CD40L signals to B cells. Consistent with this, only CD4+ T cells primed with DCs or LLPCs, but not those primed with SLPCs, helped cognate B cells to differentiate to ASCs [121]. Regarding the molecular mechanisms underlying the action of LLPCs, it can be suggested that their effect on TFH polarization might be related to their reduced capacity to prime CD4+ T cells and their reduced IL-2 signaling, which inhibit TFH differentiation by inducing STAT5-dependent expression of Blimp-1, a repressor of BCL-6 [122124].…”
Section: Function Of Pcsmentioning
confidence: 70%
“…T cells, primed with DCs or LLPCs, but not with SLPCs, can provide CD40L signals to B cells. Consistent with this, only CD4+ T cells primed with DCs or LLPCs, but not those primed with SLPCs, helped cognate B cells to differentiate to ASCs [121]. Regarding the molecular mechanisms underlying the action of LLPCs, it can be suggested that their effect on TFH polarization might be related to their reduced capacity to prime CD4+ T cells and their reduced IL-2 signaling, which inhibit TFH differentiation by inducing STAT5-dependent expression of Blimp-1, a repressor of BCL-6 [122124].…”
Section: Function Of Pcsmentioning
confidence: 70%
“…Third, they evade immune complex-mediated cell death by downregulating the death receptor FcγRIIb ( 29 ). Finally, they promote the differentiation of follicular helper T cells, so forming a positive feedback loop that amplifies humoral immunity ( 6 ). Therefore, a strategy limiting the longevity of these cells would be beneficial in controlling diseases related to long-lived PCs and plasmacytoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, when PCs reside in milieu providing survival niches for them, such as bone marrow (BM) and inflamed sites, they terminally differentiate into post-mitotic PCs attaining a life span of months or even decades ( 1 ). These long-lived PCs have been known to be crucial for long-lasting immunity in experimental animals and humans ( 2 6 ), but little is known about how they sustain viability for such a long period.…”
Section: Introductionmentioning
confidence: 99%
“…Spleen and cervical lymph node (cLN) cells from 35–40-wk-old mice were analyzed by FACS, as previously described (20). The following mAbs and reagents were purchased from BD Biosciences (San Jose, CA, USA) or eBioscience (San Diego, CA, USA): anti-CD4-PerCP, anti-Bcl6-FITC, anti-CXCR5-biotin, streptavidin-allophycocyanin (APC), anti-CD44-APC-Cy7, anti-GL7-FITC, anti-Fas-PE, anti-B220-PerCP, and anti-CD138-APC.…”
Section: Methodsmentioning
confidence: 99%